Meta-analysis of omega-3 polyunsaturated fatty acids on immune functions and nutritional status of patients with colorectal cancer - Yue, Tinghui; Xiong, Kai; Deng, Jia; Hu, Wenting; Tan, Tianying; Li, Shuangshuang; Yang, Tao; Xiao, Tianbao (Frontiers in Nutrition, 2022)
This meta-analysis assessed the clinical significance of omega-3 polyunsaturated fatty acids (PUFAs) in the management of patients with colorectal cancer (CRC) after radical resection. We comprehensively searched electronic databases, such as EMBASE, PubMed, MEDLINE and Cochrane Library, China National Knowledge Infrastructure (CNKI), China Biomedical Database (CBM), Wanfang Electronic Database, and VIP Medical Information System (VIP) from inception to 10 April 2022. Randomized controlled trials (RCTs) of omega-3 PUFAs and conventional nutrition or blank treatments were selected. The following were evaluated in the pooled analysis: immune function-related indices (IgA, IgG, IgM, CD3+, CD4+, CD8+, and ratio of CD4+/CD8+), nutritional status-related indices [total protein (TP), albumin (ALB), and prealbumin (PA)], and their corresponding 95% confidence intervals (CIs). Next, we conducted heterogeneity detection, sensitivity analysis, contour-enhanced funnel plot to detect possible publication bias, and meta-regression analysis. In all, 20 studies, including 1,613 patients (809 in the omega-3 PUFAs group and 804 in the control group), were selected in the final analysis. The results of the pooled analysis showed that omega-3 PUFAs significantly increased the humoral immune function indices, including IgA [standardized mean difference (SMD) = 0.54, 95% CI 0.10–0.99], IgM (SMD = 0.52, 95% CI 0.05–0.99), IgG (SMD = 0.65, 95% CI 0.47–0.84); T cell immune function indices, including CD3+ (SMD = 0.73, 95% CI 0.54–0.92), CD4+ (SMD = 0.76, 95% CI 0.53–0.98), and ratio of CD4+/CD8+ (SMD = 0.66, 95% CI 0.39–0.92). However, CD8+ was markedly reduced after intervention of omega-3 PUFAs (SMD = –0.28, 95% CI –0.66–0.09). In addition, pooled analysis indicated that omega-3 PUFAs markedly improved the nutritional status indicators, including TP (SMD = 0.53, 95% CI 0.17–0.88), ALB (SMD = 0.43, 95% CI 0.15–0.70), and PA (SMD = 0.46, 95% CI 0.01–0.90). The meta-regression analysis revealed that the covariates of the small sample affected the robustness and credibility of the CD4+ results. Conclusively, this study suggested that omega-3 PUFAs have the potential to be used as a valid immunonutritional therapy/support for treating patients with CRC postoperatively. This meta-analysis protocol was registered in PROSPERO (no. CRD42021288487). Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42021288487], identifier [CRD42021288487].